ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KEBIJAKAN DIVIDEN DAN DAMPAKNYA TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN MANUFAKTUR YANG TERCATAT DI BURSA EFEK INDONESIA - Nafi'ah, Zumrotun (Sekolah Tinggi Ilmu Ekonomi Semarang, 2013)
This study aimsto investigate theeffect ofownershipstructure, growth,profitability, and firm size to dividendpolicy. The study alsoexamined the effect ofthese factors to firm value throughdividend policy.The data was collectedat themanufacturingcompanieslisted on theIndonesiaStock Exchange. From 56  population of 5 manufacturing firm which pay dividend, obtained 126 companies that pay dividends during the observation period and then tested with path analysis. The results showedthat the ownership structure has significantly negative effect to dividend policy, while growth has positive and significant effect to dividendpolicy. Profitability and firm sizein this studydid notprove that have effect to dividendpolicy. The results also showedthatownership structure does not influence firm value, while firmgrowth, profitability, firm size, anddividend policyhave a positiveand significant effect to firm value. Dividend policyis avariable thatmediates theeffect ofownershipstructureand growth to dividendpolicy. Neither, avariablethat mediatesthe effectof firm size and profitability to dividendpolicy. The study concluded that investors in Indonesia tend to orient to “thebirdinthehandtheory”, investorspreferthe certainty of dividend payment, ifdividendisnotpaidtheintereston their investments will be weakandcan not effectfirm value.